THE INFLUENCES OF USING PODCASTS ON IMPROVING ENGLISH LISTENING SKILLS - Lizatria Paulinsyah; Marini Pirna Damayanti; Nabila A'zahra Kosasih (PT. Intelek Cendikiawan Nusantara, 2024)
Listening is essential for English learners, aiding in understanding spoken language and enhancing overall proficiency. Despite its significance, it is often seen as challenging and underemphasized in classrooms. Factors affecting listening comprehension include pronunciation, vocabulary, and individual differences. Modern platforms like podcasts offer flexible and convenient ways to practice listening skills, showing significant improvement in learners. Recognizing individual differences highlights the need for diverse teaching strategies. Further research on using podcasts to improve English listening skills is crucial for enhancing language learning.